Aspects and challenges of applied sport biomechanics research - Schwameder, H. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Biomechanics in general and sports biomechanics in particular, are well established scientific disciplines. Due to the wide scope of application, sport biomechanics represents a very strong area within the of biomechanical research field. The specific goals of sports biomechanics research primarily cover issues of performance enhancement, comfort, injury prevention and safety regarding elite, leisure and rehabilitation sport. Due to its specificity, the research of applied sports biomechanics is confronted with significant challenges. The specific circumstances of sport disciplines have to be considered and necessitate the development of the appropriate methodology of data collection and data analysis. A large number of sophisticated and useful solutions have already been reported for many sport disciplines. These methods have to cover the scientific demands of validity, reliability and accuracy along with the more practical issues like range of usage, complexity, costs and the amount of interference with the athletes. One important challenge in sports biomechanics is to overcome the discrepancy between reliability and validity of the collected data sets. This conflict often corresponds to the issue of collecting data in a lab or field situation. Usually, data collected in the lab are more accurate and reliable, but the validity can be substantially restricted. Data collected in the field typically provide the opposite situation: high validity, but restricted accuracy and reliability. In elite sport, the highest level of validity can only be guaranteed when data are collected during competitions; however, the regulations often hamper the usage of biomechanical methodology. To overcome these problems data should be collected in semi-competitive situations. This can be performed in field studies, but also by mimicking competitions using simulation and/or imitation conditions. Furthermore, sport biomechanists should perform detailed error estimation in each specific situation of data collection for providing detailed information on data accuracy. In the literature sophisticated solutions regarding the aspects, issues and challenges on applied sports biomechanics research have already been reported. Further examples with a specific focus on walking, mountaineering and winter sports using both lab and field studies are presented with respect to usability, validity, reliability, accuracy and error estimation.